Immunogenicity and protective efficacy of OmpA subunit vaccine against Aeromonas hydrophila infection in Megalobrama amblycephala: An effective alternative to the inactivated vaccine - Zhang, Minying; Zhang, Ting; He, Yang; Cui, Hujun; Li, Hong; Xu, Zehua; Wang, Xu; Liu, Yunlong; Li, Hongping; Zhao, Xiaoheng; Cheng, Hanliang; Xu, Jianhe; et al. (Frontiers in Immunology, 2023)
Aeromonas hydrophila is a kind of zoonotic pathogen, which can cause bacterial septicemia in fish and bring huge economic losses to global aquaculture. Outer membrane proteins (Omps) are conserved antigens of Aeromonas hydrophila, which can be developed as subunit vaccines. To evaluate the protective efficacy of inactivated vaccine and recombinant outer membrane protein A (OmpA) subunit vaccine against A. hydrophila in juvenile Megalobrama amblycephala, the present study investigated the immunogenicity and protective effects of both vaccines, as well as the non-specific and specific immune response of M. amblycephala. Compared with the non-vaccinated group, both inactivated and OmpA subunit vaccines improved the survival rate of M. amblycephala upon infection. The protective effects of OmpA vaccine groups were better than that of the inactivated vaccine groups, which should be attributed to the reduced bacterial load and enhanced host immunity in the vaccinated fish. ELISA assay showed that the titer of serum immunoglobulin M (IgM) specific to A. hydrophila up-regulated significantly in the OmpA subunit vaccine groups at 14 d post infection (dpi), which should contribute to better immune protective effects. In addition, vaccination enhanced host bactericidal abilities might also attribute to the regulation of the activities of hepatic and serum antimicrobial enzymes. Moreover, the expression of immune-related genes (SAA, iNOS, IL-1 β, IL-6, IL-10, TNF α, C3, MHC I, MHC II, CD4, CD8, TCR α, IgM, IgD and IgZ) increased in all groups post infection, which was more significant in the vaccinated groups. Furthermore, the number of immunopositive cells exhibiting different epitopes (CD8, IgM, IgD and IgZ) that were detected by immunohistochemical assay had increased in the vaccinated groups post infection. These results show that vaccination effectively stimulated host immune response (especially OmpA vaccine groups). In conclusion, these results indicated that both the inactivated vaccine and OmpA subunit vaccine could protect juvenile M. amblycephala against A. hydrophila infection, of which OmpA subunit vaccine provided more effective immune protection and can be used as an ideal candidate for the A. hydrophila vaccine.